Appropriate neck circumference cut-off points for overweight and central obesity in Turkish University students: Neck circumference cut-off points - Özkaya, Ismail; Tunckale, Aydın (Progress in Nutrition, 2021)
Background: NC is an easier and faster anthropometric measurement and has been demonstrated that there is strong correlation between NC and WC Material and Methods: In addition to our preliminary study we have demonstrated that; the NC has strong corelation with owerveight and central obesity.In this step of the preliminary study, we investigated to evaluate the correlation of the neck circumference with BMI, WC, W/H ratio and to establish cut off values of the NC for prediction of overweight and central obesity in larger population. Results: The prevalence of overweight was 17.1%. An NC of >37 cm for men and >32.5 cm for women was the best cut off point for determining subjects with overweight (P<0.001). The AUC was 0.918 for men and 0.907 for women. The prevalence of abdominal obesity was 15.1%. NC of >38.5 cm for men and >33.5cm for women was the best cut-off point for determining subjects with obese (P<0.001). Conclusions: NC >37 cm for men and >32.5 cm for women was the best cut-off point to determine subjects with overweight and a NC >38.5 cm for men and >33.5cm for women was the best cut-off point to determine subjects with central obesity. Key Words: Neck circumference, Waist circumference, Central Obesity, Overweight, Cut-off